Microrefugia and species persistence in the Galápagos highlands: a 26,000-year paleoecological perspective - Collins, Aaron F.; Bush, Mark B.; Sachs, Julian P. (Frontiers in Genetics, 2013)
The Galápagos Islands are known to have experienced significant drought during the Quaternary. The loss of mesophytic upland habitats has been suggested to underlie the relatively lower endemism of upland compared with lowland plant assemblages. A fossil pollen record spanning the last 26,000 years from an upland bog on Santa Cruz Island, revealed the persistent presence of highland pollen and spore types during the last glacial maximum and a millennial-scale series of droughts in the mid Holocene. The absence of lowland taxa and presence of mesic taxa led to the conclusion that the highland flora of the Galápagos persisted during both these periods. The resiliency of the highland flora of the Galápagos to long-term drought contradicts an earlier hypothesis that an extinction of highland taxa occurred during the last glacial maximum and that rapid Holocene speciation created the modern plant assemblage within the last 10,000 years. Based on the palynological data, we suggest that, even during the height of glacial and Holocene droughts, cool sea-surface temperatures and strong trade-wind activity would have promoted persistent ground level cloudiness that provided the necessary moisture inputs to maintain microrefugia for mesophytic plants. Although moist conditions were maintained, the lack of precipitation caused the loss of open water habitat during such events, and accounts for the known extinctions of species such as Azolla sp., and Elatine sp., while other moisture dependent taxa, i.e., Cyathea weatherbyana, persisted.